Oblique subjects in Croatian: are they subjects enough? - Zovko Dinković, Irena (2012)
The so-called oblique or dative subjects in Croatian may appear in the genitive, accusative or, most often, dative case. The focus of this paper is on the oblique subjects in the accusative and dative case such as (1) and (2) respectively : (1) Petra je strah vode. Peter-ACC is fear water 'Peter is afraid of water.' (2) Hladno mi je. cold I-DAT is 'I'm cold.' These arguments in Croatian show two anomalous coding properties with regard to typical nominative subjects: oblique case marking and lack of congruence. They fit well into the pragmatic definition of subject as topic but provide less consistent evidence as to their grammatical status, eg. they cannot be controllers of reflexivization, and although they can be controllers of implicit subjects of infinitival complement clauses, the same can be said of direct and indirect objects. The semantics of dative subject constructions in Croatian is also inconsistent: they are all Experiencers, but some are involved in constructions where the dative is the single referent of an involuntary external influence, whereas others involve a different kind of subjective experience, as in (3) Čudno mi je da si došao. strange I-DAT is that you came. 'I find it strange that you came.' The aim of this paper is therefore twofold: first, to refine the existing semantic interpretation of dative subjects in Croatian ; and second, to argue, through the analysis of different subjecthood criteria applied to dative subjects (cf. Keenan, 1976), that there is no sufficient evidence for oblique subjects to be considered a viable syntactic category in Croatian. In doing this we rely on functionalist interpretations (cf. Comrie, 1981) of subject in terms of prototypes and further support a claim by Kučanda and Omazić (1999) that the so-called oblique subjects form a continuum where at one end we find languages with highly grammaticalized pragmatic function of topic, such as Modern Icelandic (cf. Zaenen, Maling and Thràinsson, 1985), and at the other end languages such as Croatian, where pragmatic topics are not grammaticalized as subjects. References: Comrie, Bernard (1981) Language Universals and Linguistic Typology, Oxford: Basil Blackwell Keenan, Edward L. (1976) 'Towards a Universal Definition of Subject', in: Ch. N. Li (ed.) Subject and Topic, New York and London: Academic Press, pp. 303-333 Kučanda, Dubravko and Marija Omazić (1999) 'Subjekt u kosom padežu: koliko sintakse, a koliko pragmatike?', Teorija i mogućnosti primjene pragmalingvistike, Ivanetić, Nada, Boris Pritchard and Diana Stolac (eds.), Zagreb and Rijeka: Hrvatsko društvo za primijenjenu lingvistiku, pp. 439-448 Zaenen, Annie ; Joan Maling and Höskuldur Thràinsson (1985) 'Case and Grammatical Functions. The Icelandic Passive', Natural Language and Linguistic Theory 3:4, pp. 441-483